Rapid differentiation of Mycobacterium xenopi from mycobacteria of the Mycobacterium avium-intracellulare complex by pyrolysis mass spectrometry. Issue 4 (April 1992) - Sisson, P R; Freeman, R; Magee, J G; Lightfoot, N F
Abstract : Thirty four cultures of slow growing, Tween-80 negative mycobacteria were analysed by pyrolysis mass spectrometry. The results showed that pyrolysis mass spectrometry could positively distinguish strains of Mycobacterium xenopi from those of the Mycobacterium avium-intracellulare (MAI) complex. Pyrolysis mass spectrometry may be a useful technique for the rapid characterisation of non-tuberculous mycobacteria in such clinical settings as their isolation from immunocompromised patients-for example, those with AIDS.